Formulasi Dan Uji Mutu Fisik Ekstrak Etanol Rimpang Kunyit Putih (Curcuma Zedoaria) Pada Sediaan Tablet Dengan Variasi Bahan Polivinil Pirolidon Dan Starch 1500 - Rika, Putu; Juliadi, Debby; Putra, I Made Agus Sunadi (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
The white turmeric plant (Curcuma zedoaria) is a species from the Zingiberaceae family which is very important in traditional medicine and the medicinal industry. Apart from being used as a food or beverage ingredient, white turmeric is also used as a traditional medicine, such as stomach ache medicine, stomach booster, fever reducer and can treat skin diseases. This study aims to determine the effect of the concentration of polyvinyl pyrrolidone binder and starch 1500 disintegrating agent on the physical properties of tablets and to obtain a white turmeric rhizome ethanol extract tablet formula which has the best physical quality test. The method used in the manufacture of tablets is the wet granulation method, because this method can improve flow properties and increase compressibility. The results of this study on the physical quality testing of FI and FIII tablets have fulfilled the physical quality test requirements for tablets, but FII has not fulfilled the physical quality test requirements for tablet preparations because FII does not meet the disintegration time test requirements, this is influenced by the concentration of polyvinyl pyrrolidone binder (PVP) was higher than Starch 1500 disintegrant. In this study, FIII had the best physical quality test, where FIII was a physical quality test and had the fastest tablet disintegration time, which was 10 minutes. This is influenced by the higher concentration of Starch 1500 disintegrant, which is 8% compared to the polyvinyl pyrrolidone (PVP) binder, which is 5%.